The nature of borders : salmon, boundaries, and bandits on the Salish Sea - Wadewitz, Lissa K. (Emil and Kathleen Sick lecture-book series in western history and biography., 2012)
For centuries, borders have been central to salmon management customs on the Salish Sea, but how those borders were drawn has had very different effects on the Northwest salmon fishery. Native peoples who fished the Salish Sea drew social and cultural borders around salmon fishing locations and found ways to administer the resource in a sustainable way. Nineteenth-century European settlers took a different approach and drew the Anglo-American border along the forty-ninth parallel, ignoring the salmon's patterns and life cycle. As the canned salmon industry grew and more people moved into the region, class and ethnic relations changed. The Nature of Borders is about the ecological effects of creating cultural and political borders.-- Publisher description.